No. 110 10.4.93-10.7.93 or Polish uncreative writing - Marecki, Piotr (MatLit, 2016)
This article provides an overview of Polish digital literature, using the tools and vocabulary of uncreative writing put forward by American artist and theorist Kenneth Goldsmith. The analysis covers appropriation techniques, plagiarism types, and the thinkership of conceptual writing practices. The selected works use various media and explore diverse textual materialities, which depend on specific platforms, such as the MERA 300 minicomputer, the Wikipedia platform, or JavaScript. The pieces are described in terms of database studies in contemporary digital literature.